2015
DOI: 10.1002/mnfr.201500071
|View full text |Cite
|
Sign up to set email alerts
|

Cor a 14, the allergenic 2S albumin from hazelnut, is highly thermostable and resistant to gastrointestinal digestion

Abstract: ScopeAllergens from nuts frequently induce severe allergic reactions in sensitive individuals. The aim of this study was to elucidate the physicochemical characteristics of natural Cor a 14, the 2S albumin from hazelnut.Methods and resultsCor a 14 was purified from raw hazelnuts using a combination of precipitation and chromatographic techniques. The protein was analyzed using gel electrophoresis, MS, and far‐UV circular dichroism (CD) analyses. The immunoglobulin E (IgE) binding of native, heat‐treated, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 37 publications
(55 reference statements)
4
39
0
Order By: Relevance
“…The purified allergens were detected by SDS-PAGE and confirmed by the immunoblotting with the specific IgG polyclonal antibodies (pAb) prepared previously ( Figure 2). 5,9,11 Figure 1B describes the prevalence of crab myosinogen allergens among the 398 AC subjects, and the proportions of subjects allergic to AK, SCP, TIM, and FLN c were 24.87% (n = 99), 18.34% (n = 73), 19.10% (n = 76), and 25.13%…”
Section: Ige Reactivity Of the Patients' Sera To Allergens Isolatedmentioning
confidence: 99%
See 2 more Smart Citations
“…The purified allergens were detected by SDS-PAGE and confirmed by the immunoblotting with the specific IgG polyclonal antibodies (pAb) prepared previously ( Figure 2). 5,9,11 Figure 1B describes the prevalence of crab myosinogen allergens among the 398 AC subjects, and the proportions of subjects allergic to AK, SCP, TIM, and FLN c were 24.87% (n = 99), 18.34% (n = 73), 19.10% (n = 76), and 25.13%…”
Section: Ige Reactivity Of the Patients' Sera To Allergens Isolatedmentioning
confidence: 99%
“…Food allergens contain both conformational and linear epitopes. Linear epitopes are relevant for immunoreactivity in gastrointestinal food allergies . Peptide micro‐arrays provide a tool for mapping linear IgE epitopes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high stability against in vitro digestion has been described for 2S albumins and LTPs from several allergenic foods [23,25,49,50]. Concerning the digestion of hazelnut allergens, Vieths et al also observed a high resistance of the prolamin fraction, with retained IgE binding for proteins in the prolamin molecular size range [20], and Pfeifer et al recently reported that isolated Cor a 14 withstood simulated gastric and intestinal digestion [51]. Differently to these former studies, Cor a 14 and Cor a 8 were shown to be degraded by intestinal enzymes in our model system, a deviation that might again be explained by our model system, which more closely reflects the physiological situation, and by subjecting the whole food matrix towards digestion (instead of isolated proteins), which has been discussed as an influence on single protein digestibility in another recent study [26].…”
Section: Differential Stability Of Allergen Super(families) Under Gasmentioning
confidence: 99%
“…Both, far and near CD spectra have been useful in monitoring thermal stability of food allergens, i.e. thermal stability of Cor a 14, the 2S albumin from hazelnut . The effects of high‐pressure/temperature treatment and pulsed electric field treatment on peanut Ara h 2 and 6 and apple Mal d 3 and 1b were examined by CD spectroscopy and the results showed that novel processing technologies had little effect on the allergen structure.…”
Section: Introductionmentioning
confidence: 99%